Factors Affecting the Incidences of Needle Stick Injury on The Nurses Emergency Department of Hospital East Java - Adity Adha Putra1 , Ni’matu Zuliana1 , Zikri Fathur Rahman1 , Noeroel Widajati1 , Abdul Rohim Tualek (Institute of Medico-legal Publications Pvt Ltd, 2020)
Hospital with all the facilities and equipment that can be a source of health and safety hazards of potential, especially for health workers if no management following the standards of safety and health procedure kerjaNeedle stick and sharp object injuries is a significant challenge for health workers, and nurses are jobs are most often associated with the incidence of needle stick injury. The purpose of this study was to determine the factors that influence the prevalence of needle stick injury to nurses in the emergency department of hospital Eas Java. This study using 64 samples from a total of as many as 76. The ER nurse that most of the variables age category ? 29 years, ? five years of working life, has never participated in occupational safety and health training, and education level diploma 3 — workers who perform unsafe actions as much as 37.5%. The Bivariable analysis showed that age, work periode, education level, and training has a significant value above 0.05 was no meaningful relationship to the needle stick injury. Unsafe action was a value of 0.026, which means significance was a substantial relationship with a needle stick injury. The multivariable nurses who perform dangerous activities are at increased risk of needle stick injury 4x compared to nurses who work safely. Prevention of occupational accidents to human factors include labor regulations taking into account the limits of the abilities and skills of workers, nullify the things that reduce the concentration of workers, enforce work discipline, avoid actions that bring accidents and eliminate their physical and mental incompatibility.